2013
DOI: 10.3758/s13414-013-0435-z
|View full text |Cite
|
Sign up to set email alerts
|

Expert anticipation from deceptive action

Abstract: Expertise in sports enhances the ability to anticipate forthcoming events from the observation of a player's actions. In the present study, we investigated whether this ability is applicable to deceptive action. In three experiments, performance at anticipating the direction change of a running opponent was examined with experienced rugby players and novice counterparts. These experiments were conducted with reaction-time and temporal-occlusion tasks, in combination with eye movement recordings and the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 50 publications
9
79
0
Order By: Relevance
“…That is, the head fake had a similar impact (i.e., the size of the head-fake effect was not reduced) on the performance of basketball players, as compared to soccer players and nonathletes. This pattern of results supports previous studies showing that performance of expert athletes suffers under time pressure, when they are confronted with a deceptive action (Dicks et al 2010;Mori & Shimada, 2013;Ripoll et al 1995).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…That is, the head fake had a similar impact (i.e., the size of the head-fake effect was not reduced) on the performance of basketball players, as compared to soccer players and nonathletes. This pattern of results supports previous studies showing that performance of expert athletes suffers under time pressure, when they are confronted with a deceptive action (Dicks et al 2010;Mori & Shimada, 2013;Ripoll et al 1995).…”
Section: Discussionsupporting
confidence: 81%
“…These show, for example, that soccer goalkeepers save fewer penalty kicks in deceptive trials than in non-deceptive trials (Mori & Shimada, 2013) and that French boxers produce more false alarms to a fake attack (Ripoll et al 1995). Thus, there is some evidence that the performance of expert athletes also suffers under time pressure when they are confronted with a deceptive action.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Observers of a soccer player are able to predict the kick direction before the footto-ball contact (24). Deception in rugby runners is detected above chance before the runner changes direction (19). More closely related to the present task, a competitive reaching study showed that preparatory cues (i.e., movements and postural configurations preceding the lift-off of the finger) give opponents an advantage (13).…”
Section: Experiments 4: How Early Is the Attention Control Signal Avaimentioning
confidence: 92%
“…For example, how one reaches for a Lego piece allows a partner to predict the intention to cooperate or compete (18). The kinematics of running reveals the intention to deceive a sports opponent (19). Observers are able to perceive the value of the poker hand in the arm kinematics of players (20).…”
Section: Methodsmentioning
confidence: 99%